2010
DOI: 10.1371/journal.pcbi.1000649
|View full text |Cite
|
Sign up to set email alerts
|

Blurring of High-Resolution Data Shows that the Effect of Intrinsic Nucleosome Occupancy on Transcription Factor Binding is Mostly Regional, Not Local

Abstract: Genome wide maps of nucleosome occupancy in yeast have recently been produced through deep sequencing of nuclease-protected DNA. These maps have been obtained from both crosslinked and uncrosslinked chromatin in vivo, and from chromatin assembled from genomic DNA and nucleosomes in vitro. Here, we analyze these maps in combination with existing ChIP-chip data, and with new ChIP-qPCR experiments reported here. We show that the apparent nucleosome density in crosslinked chromatin, when compared to uncrosslinked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
3
15
0
5
Order By: Relevance
“…6B). This conclusion is in line with recent studies showing that, at least for some TFs, their occupancy predictions can be improved by taking into account the competition with histones for DNA binding (Narlikar et al 2007;Gordan et al 2009;Raveh-Sadka et al 2009;Wasson and Hartemink 2009;Goh et al 2010;Locke et al 2010;John et al 2011;Kaplan et al 2011;Li et al 2011;Zhou and O'Shea 2011;Lickwar et al 2012;He et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…6B). This conclusion is in line with recent studies showing that, at least for some TFs, their occupancy predictions can be improved by taking into account the competition with histones for DNA binding (Narlikar et al 2007;Gordan et al 2009;Raveh-Sadka et al 2009;Wasson and Hartemink 2009;Goh et al 2010;Locke et al 2010;John et al 2011;Kaplan et al 2011;Li et al 2011;Zhou and O'Shea 2011;Lickwar et al 2012;He et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Many of the bound TFbinding sites reside in NFRs where accessibility is increased due to the low nucleosome occupancy, making it thermodynamically more favorable for TFs to bind (4,54,96,207). The in vitro reconstitution of the yeast genome into nucleosomes revealed that part of the nucleosome depletion observed at TF-binding sites is intrinsically encoded in the genome, through the DNA sequence preferences of nucleosomes.…”
Section: Transcription Factorsmentioning
confidence: 99%
“…Анализ расположения кластеров относительно генов с помощью таких инструментов, как GREAT (Genomic Regions Enrichment of Annotations Tool), дает возможность оценить расположение сайтов связывания отдельных факторов и кластеров сайтов относительно генов (Guo et al, 2012), классифицировать их как промоторные и дистальные, что является дополнительной функциональ-ной характеристикой таких кластеров. Дополнительные характеристики нуклеотидных последовательностей для описания кластеров сайтов связывания, таких как участки низкой сложности текста (Orlov, Potapov, 2004;, нуклеосомная упаковка (Орлов и др., 2006; Goh et al, 2010), позволяют более точно определить регуля-торные районы в геноме и выполнять их поиск на основе непрямых данных, без экспериментов ChIP-seq. Интегра-ция геномных данных средствами UGENE (Vas'kin et al, 2011;Васькин и др., 2012;Golosova et al, 2014) позволит качественно решать новые задачи комбинаторного анализа сайтов по данным проектов ENCODE (https://genome.ucsc.…”
Section: заключениеunclassified
“…Первые работы основывались на вы-явлении олигонуклеотидных мотивов и были ограничены статистической базой (десятки, в лучшем случае сотни последовательностей в базах данных) (Heinemeyer et al, 1998). Появление полногеномных методов секвенирова-ния дало толчок к поиску сайтов и регуляторных районов с помощью геномных профилей ChIP-seq, определению предпочтений геномной локализации, нуклеосомной упаковки (Goh et al, 2010;Орлов, 2014).…”
unclassified